Health Promotion in Health Care – Vital Theories and Research 2021
DOI: 10.1007/978-3-030-63135-2_10
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-Patient Interaction: A Vital Salutogenic Resource in Nursing Home Care

Abstract: We are now witnessing a major change in the world’s population. Many people globally grow very old: 80, 90, and 100 years. Increased age is followed by an increased incidence of functional and chronic comorbidities and diverse disabilities, which for many leads to the need for long-term care in a nursing home. Quality of life and health promotive initiatives for older persons living in nursing homes will become ever more important in the years to come. Therefore, this chapter focuses on health promotion among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 101 publications
(156 reference statements)
1
21
0
Order By: Relevance
“…Moreover, Snowden et al, (2018) found that being able to talk to somebody about what is on your mind is crucial and the only necessary in spiritual care. Hence, talking to nurses, also termed nurse–patient interaction (Haugan, 2021), and others about what is on one’s mind seem essential to well-being among NH residents (Haugan et al, 2020). Professionals in NHs should facilitate possibilities for NH residents to have visitors and contact with friends and family.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Snowden et al, (2018) found that being able to talk to somebody about what is on your mind is crucial and the only necessary in spiritual care. Hence, talking to nurses, also termed nurse–patient interaction (Haugan, 2021), and others about what is on one’s mind seem essential to well-being among NH residents (Haugan et al, 2020). Professionals in NHs should facilitate possibilities for NH residents to have visitors and contact with friends and family.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Snowden et al, (2018) found that being able to talk to somebody about what is on your mind is crucial and the only necessary in spiritual care. Hence, talking to nurses, also termed nurse-patient interaction (Haugan, 2021), and others about what is on one's mind seem essential to well-being among NH residents (Haugan et al, 2020). Professionals in NHs should facilitate possibilities for NH residents to have visitors and contact with friends and family.…”
Section: Discussionmentioning
confidence: 99%
“…Existential loneliness can also arise when people lack previous experiences relevant to their present situation or in times of uncertainty such as during an illness (Sundström et al, 2019). This description might be suitable to the experience of old people living in NHs, but at the same time, NH residents also need to spend time alone in silence talking to themselves and resting their minds (Drageset et al, 2017;Haugan, 2014aHaugan, , 2021. The present results disclosed the lowest scores for perceived meaning in life, feeling valuable, and being able to contribute to others, as well as engaging in one's surroundings and meaningful activities.…”
Section: Discussionmentioning
confidence: 99%
“…Such acceptance derives from meaningful dialogues about one's daily experiences as well as the experiences throughout one's life journey, namely opportunities to talk about ‘what is on one's mind’, which is termed the core of spiritual care (16). Therefore, nurse–patient interaction performs as a health‐promoting asset in NHs (13–15), supporting both ST, meaning‐in‐life and wellbeing in this specific context. Consequently, health professionals need knowledge about meaning‐in‐life, ST and nurse–patient interaction, and guidance in how to facilitate wellbeing by means of these approaches.…”
Section: Implications For Nursing Practicementioning
confidence: 99%
“…Research has shown that among religious/spiritual as well as non‐religions/non‐spiritual individuals, ‘being able to talk about what was on my mind’ was deemed most important. Being listened to, having one's faith/beliefs valued and being understood are all important aspects of health‐promoting nurse–patient interaction (13–15). Nevertheless, being able to talk about what was on one's mind has been reported the most important aspects of spiritual care (16).…”
Section: Introductionmentioning
confidence: 99%